Ocular Mucus Membrane Pemphigoid: A Primary Versus Secondary Entity. Issue 3 (24th March 2023) - Philip, Andrew M.; Fernandez-Santos, Carla C.; Ramezani, Koosha; Dolinko, Andrew H.; Manhapra, Ambika; Look-Why, Sydney; Chang, Peter Y.; Foster, C. Stephen; Anesi, Stephen D.
Abstract : Purpose: The purpose of this review was to investigate the idea that inflammatory events of the conjunctiva and ocular surface may act as triggering events for the onset of ocular mucus membrane pemphigoid (oMMP). Methods: A retrospective chart review of patients with biopsy-proven oMMP and no systemic pemphigoid disease. The presence, or absence, of the following inflammatory conditions at the time of OMMP diagnosis was noted: significant eyelid disease, significant atopic eye disease, Stevens–Johnson syndrome, graft-versus-host disease, viral keratitis, sarcoidosis with ocular involvement, chemical burns, medicamentosa, Sjogren syndrome, systemic lupus erythematosus with ocular involvement, and epidemic keratoconjunctivitis. Response to immunomodulatory therapy (IMT) was also recorded. Results: A total of 779 patient records were identified. Conjunctival biopsy was present in 724 patients, with 646 (89.2%) being positive. One hundred thirty-nine patients (21.5%) with positive biopsies had extraocular pemphigoid disease and were excluded from further analysis. Of the 507 included patients, 154 (30.4%) had at least one of the specified inflammatory conditions present at the time of OMMP diagnosis. One hundred eighteen patients (23.3%) had only 1 such condition, 35 (6.9%) had 2, and 1 patient had 3. In patients with at least one of these conditions present, response to IMT was seen in 84.9% of patients with sufficient follow-up. Conclusions: Our study suggests that oMMP may arise as a secondary pathology to acute inflammatory events or chronic inflammatory states of the conjunctiva and ocular surface.